Depression and its Associated Factors among Faculties of Academic Institutions - Sharma, Bimala; Shrestha, Nirmala; Sah, Saurabh Kishor (Journal of Nepal Health Research Council, 2023)
Background: Depression is one of the common mental disorders occurring frequently in the community. The study aimed to find out the prevalence and correlates of depression among faculties of academic institutions in Pokhara Metropolitan, Kaski, Nepal. Methods: A cross-sectional study was conducted among 416 faculties selected from six academic institutions of Pokhara Metropolitan. A self-administered structured questionnaire method was applied to assess depression and explanatory variables among respondents. Beck Depression Inventory (BDI) was used to measure depression. The BDI score was classified into normal, mild, moderate and severe depression using the standard classification; and the depression levels were dichotomized into “absent” and “present”. Descriptive statistics, bivariate analysis and multivariate logistic regression analysis were computed. Level of significance was set at 5%. Results: Of the total, 21.6% of respondents had depression including 6.7% moderate and 2.9% severe type depression. The likelihood of reporting depression was significantly higher among those who had physical health problems (AOR, 2.88; 95% CI, 1.16-7.13), consumed vegetables less than 2 times a day (AOR, 2.34; 95% CI, 1.07-5.08), had limited access to teaching aids in workplace (AOR, 2.00; 95% CI 1.19-3.33), had higher job stress and higher COVID-19 fear. Depression did not differ by the socio-demographic characteristics of the respondents and type of institution. Conclusions: Improving physical health conditions, promoting vegetable consumption, ensuring access to basic facilities, and creating an enabling environment at workplace may help to address depression among faculties. Regular screening programs may help for timely identification and management of the cases. Keywords: Academic institutions; depression, faculties; job stress